2016
DOI: 10.1021/acs.chemmater.6b03872
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Bactericidal Activity of Poly(arginine)/Hyaluronan Nanolayered Coatings

Abstract: The number of nosocomial infections related to implants and medical devices increase alarmingly worldwide. New strategies based on the design of antimicrobial coatings are required to prevent such infections. Polyelectrolyte “multilayer” films constitute a powerful tool for nanoscale surface functionalization which allows addressing this issue. By investigating films built up with poly­(arginine) (PAR) of various chain lengths (10, 30, 100, and 200 residues) and hyaluronic acid (HA), we demonstrate that exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…It is worth noting that the fungicidal activity would likely benefit from the substitution of lysine with arginine residues, provided that previous works have demonstrated the superior cell permeability by arginine polymers over lysine-containing ones [33,34]. Mechanistic evidences indicate that arginine can enhance the activity of both translocating and membrane permeabilizing peptides [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the fungicidal activity would likely benefit from the substitution of lysine with arginine residues, provided that previous works have demonstrated the superior cell permeability by arginine polymers over lysine-containing ones [33,34]. Mechanistic evidences indicate that arginine can enhance the activity of both translocating and membrane permeabilizing peptides [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Mutschler et al found that the length of poly(arginine), a cationic polypeptide, in (poly(arginine)/HA) LbL films played a key role in the antibacterial effect of these films. Low‐MW poly(arginine) consisting of 30 repeat units was hypothesized to diffuse to the surface of the film and interact with surface exposed bacteria due to enhanced mobility compared to 100 and 200 repeat unit poly(arginine) films . Based on the intrinsic antibacterial properties of PLL and the findings of these previous studies, we hypothesized that PLL/HA assemblies may serve as antibacterial coatings that inhibit planktonic bacterial growth and bacterial surface attachment by a mechanism influenced by PLL mobility.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] The hydrophilicity 13 of the films, as well as their rigidity, 11,14 can be tuned by the adjustment of physico-chemical parameters of the film buildup, such as pH and/or ionic strength. Knowing that bacterial membranes are negatively charged, most of contact-killing LbL films were developed ending with positively charged polyelectrolytes [15][16][17][18] or quaternary ammonium containing polymers. [19][20] The bactericidal effect of these films is governed by the surface composition 13,16 or the diffusion of polycations in the films.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20] The bactericidal effect of these films is governed by the surface composition 13,16 or the diffusion of polycations in the films. [17][18]21 Release-killing LbL films leach out antibacterial agents, by direct diffusion [22][23] or by film degradation due to hydrolysis, [24][25] pH 26 or enzymes. 27 Since a few decades, an intensive research is being carried out to explore the potential of polyphenols, found in plants as secondary metabolites, as antibacterial and antioxidants agents.…”
Section: Introductionmentioning
confidence: 99%